From Monochrome to Technicolor Simple Generic Approaches to Multicomponent Protein Nanopatterning Using Siloxanes with Photoremovable Protein-Resistant Protecting Groups - El Zubir, Osama (Langmuir : the ACS journal of surfaces and colloids, 2017)
We show that sequential protein deposition is possible by photodeprotection of films formed from a tetraethylene-glycol functionalized nitrophenylethoxycarbonyl-protected aminopropyltriethoxysilane (NPEOC-APTES). Exposure to near-UV irradiation removes the protein-resistant protecting group, and allows protein adsorption onto the resulting aminated surface. The protein resistance was tested using proteins with fluorescent labels and microspectroscopy of two-component structures formed by micro- and nanopatterning and deposition of yellow and green fluorescent proteins (YFP/GFP). Nonspecific adsorption onto regions where the protecting group remained intact was negligible. Multiple component patterns were also formed by near-field methods. Because reading and writing can be decoupled in a near-field microscope, it is possible to carry out sequential patterning steps at a single location involving different proteins. Up to four different proteins were formed into geometric patterns using near-field lithography. Interferometric lithography facilitates the organization of proteins over square cm areas. Two-component patterns consisting of 150 nm streptavidin dots formed within an orthogonal grid of bars of GFP at a period of ca. 500 nm could just be resolved by fluorescence microscopy